Education and the soul : toward a spiritual curriculum - Miller, John P., 1943- (State University of New York Press, 2000)
"Education and the Soul is the first book to comprehensively address how the soul can be nourished in educational settings. The book explores the nature of the soul and offers teaching/learning approaches that can be used to nurture the development of students' souls. It also examines how institutions such as schools have souls and what can be done to care for a school's spiritual life."--Jacket